Comparison of Knowledge Sufficiency Regarding the Specialty of Prosthodontics Among Health Care Professionals of Karachi: Comparison of Knowledge Sufficiency Regarding the Specialty of Prosthodontics - Yasin, Osama; Baqar, Anum; Ilyas, Farnaz; Hakeem, Saman; Faisal Fahim, Muhammad (Pakistan Journal of Health Sciences, 2022)
A chunk of people from general public and health care professionals know about Prosthodontics as one of the essentials of dentistry and hence, the patients are not adequately referred to them. Subsequently, the quality of oral rehabilitation is negatively affected. Objective: Therefore, the aim was to assess and compare the level of knowledge related to Prosthodontics among various healthcare professionals in Karachi. Methods: This cross-sectional study using a voluntarily filled validated questionnaire was disseminated to various health care professionals. The selection of participants was in an equal ratio of various health professional communities and were categorized into 5 groups: medical professionals (MBBS), fraternity of doctor of physical therapy (DPT), personnel of doctor of pharmacy (Pharm- D), medical laboratory technicians (MLT) and faculty of nursing. The core results were interpreted in terms of descriptive analysis whereas the inter-group comparison of data was done through ANOVA test application to compare the level of knowledge among various health care professionals. Results: Superficially, 72% health care professionals knew about Prosthodontics through newspaper. The inter-group comparison showed that there is a significant difference in the comprehensive knowledge about Prosthodontics among all health care professionals. Among them, DPT and MLT professionals were found to be at the higher level of knowledge status than those of MBBS, nursing and pharmacy. Conclusions: The specialty of Prosthodontics is still searching for its identity rather among the health care providers than among the general public.